Links between household food consumption and nutritional status of children aged 6–59 months: a case study in Burkina Faso - Kouame, Jean S. R.; Compaore, Ella W. R.; Blaney, Sonia; Bambara, Estelle A.; Ouedraogo, Issaka; Sidibe, Hamidou; Dicko, Mamoudou H. (Frontiers in Nutrition, 2025)
IntroductionFood insecurity is a major challenge in many developing countries and may impede the achievement of Sustainable Development Goal 2 (SDG2). Nearly 15% of Burkina Faso’s population is facing food insecurity. In 2021, 21.6% of children under the age of five (U5) were stunted. This rate remains high. This study aimed to investigate the relationship between Global Acute Malnutrition (GAM) and socio-demographic, economic, and household dietary factors among U5 children in the Sanguié Province in Burkina Faso.MethodsThe method used is based on a quantitative cross-sectional study using primary data on food and nutritional security for 237 children under the age of 5 from 150 households. Data analysis was carried out sequentially: a first univariate descriptive stage was used to characterize the variables studied, with a prevalence of MAG [11.4% (7.35–15.44)], which is higher than the 10% alert threshold set by the WHO; this stage is followed by a bivariate analysis to explore their associations. Finally, a multiple correspondence analysis (MCA) was carried out to identify the independent factors associated with acute malnutrition because of its ability to study complex relationships between variables and to represent their structure in the form of factorial spaces.Results and discussionFindings indicate that malnutrition is associated with high household food expenditure; medium dietary diversity; a medium/high demographic dependency ratio; the absence of toilets; and food reserves that cover less than 6 months. These findings highlight the need to strengthen food security by fostering household economic development and to ensure optimal access to improved sanitation.